1992
DOI: 10.1002/jlb.52.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Production of macrophage colony-stimulating factor by adult murine parenchymal liver cells (hepatocytes)

Abstract: The activity of macrophage colony-stimulating factor (M-CSF) was found in the culture supernatant of mouse parenchymal liver cell fractions in a bone marrow colony-forming assay. The activity of an M-CSF-like substance purified by a four-step procedure was neutralized by goat anti-mouse M-CSF antiserum. M-CSF mRNA was detected in cellular RNA prepared from cultured parenchymal liver cell fractions by Northern blot analysis and also in cultured parenchymal liver cells by in situ hybridization. These results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 1 publication
4
14
0
Order By: Relevance
“…These data provide evidence to the facts that GM-CSF is essential for inducing chemotaxis of monocytes into granulomas, their differentiation into macrophages, and survival of macrophages within the granulomas. Previous studies showed that GM-CSF is constitutively produced by hepatocytes, Kupffer cells, fibroblasts, and sinusoidal endothelial cells, [71][72][73][74][75][76][77] in agreement with the results of the present study that the in situ hybridization method showed positive signals in vascular endothelial cells, hepatocytes, and granuloma cells in the liver of GM-CSF ϩ/ϩ mice. However, GM-CSF is not demonstrated at message level in the liver tissues of GM-CSF-deficient mice.…”
Section: Discussionsupporting
confidence: 93%
“…These data provide evidence to the facts that GM-CSF is essential for inducing chemotaxis of monocytes into granulomas, their differentiation into macrophages, and survival of macrophages within the granulomas. Previous studies showed that GM-CSF is constitutively produced by hepatocytes, Kupffer cells, fibroblasts, and sinusoidal endothelial cells, [71][72][73][74][75][76][77] in agreement with the results of the present study that the in situ hybridization method showed positive signals in vascular endothelial cells, hepatocytes, and granuloma cells in the liver of GM-CSF ϩ/ϩ mice. However, GM-CSF is not demonstrated at message level in the liver tissues of GM-CSF-deficient mice.…”
Section: Discussionsupporting
confidence: 93%
“…However, the present study showed that not only CSF receptors were insignificantly increased or even sharply decreased in mRNA abundance in most of eight liver cells, but also the ex-pression of CSF family members in the eight liver cells differed from above findings to some extent. For example, the mRNA abundance of CSF1 was decreased in HC, which was quite opposite to the result of Tsukui et al (1992); CSF2 was highly expressed during LR in other liver cells except for DC, where this was basically consistent with a previous report; CSF3 was upregulated in other liver cells with the exception of SEC, which is largely consistent with the report by Dame et al (2002) that both HC and nonparenchymal cells can secrete CSF. Notably here, there is very little evidence that CSF are synthesized in BEC, but it is interesting that our results showed a high expression of CSF1-3 in BEC.…”
Section: Discussionsupporting
confidence: 90%
“…In the literature, there are also reports that, within the regenerating liver, oval cells express CSF3 and its receptor, while sinusoidal endothelial cells (SEC) upregulate expression of CSF2 and its receptor CSF2R (Dame et al, 2002;Meng et al, 2012). A significant production of CSF1 has been discovered in hepatocytes, besides Kupffer cells (Tsukui et al, 1992). However, the present study showed that not only CSF receptors were insignificantly increased or even sharply decreased in mRNA abundance in most of eight liver cells, but also the ex-pression of CSF family members in the eight liver cells differed from above findings to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that both macrophage growth factors are expressed at the message level regardless of MSR-A deficiency, because M-CSF and GM-CSF are known to be produced by hepatocytes, Kupffer cells, and sinusoidal endothelial cells 66,67 and because expression of M-CSF mRNA was also reported in Kupffer cell-depleted and control mice. 26 The present investigation has demonstrated that MSR-A deficiency impairs the uptake of C. parvum by Kupffer cells and monocyte-derived macrophages and thus induces a marked delay in hepatic granuloma formation in MSR-A-deficient mice.…”
Section: Discussionmentioning
confidence: 64%